Holistic Management of Peptic Ulcer Disease: A Multidisciplinary Perspective - Pradnya Deolekar; Kavitha Dongerkery (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Peptic ulcer disease (PUD) is a global health problem, affecting millions of people worldwide. An infected individual has an estimated lifetime risk of 10 -20% for the development of peptic ulcer disease, which is at least 3-4-fold higher than in non-infected subjects. PUD, characterized by mucosal erosions in the stomach or duodenum, remains a prevalent health issue. This review provides a comprehensive overview of both conventional and alternative treatment strategies. Proton pump inhibitors (PPIs) are the mainstay of pharmacotherapy, effectively reducing gastric acid production and promoting ulcer healing. H2 receptor antagonists serve as alternatives, inhibiting histamine-induced acid secretion. For Helicobacter pylori infections, antibiotic regimens are essential for eradication and recurrence prevention. Symptomatic relief and mucosal protection are further supported by antacids and cytoprotective agents. In addition to these conventional treatments, alternative therapies such as Ayurvedic, herbal, and homeopathic approaches have gained attention. Ayurvedic treatments often focus on dietary modifications and herbs like licorice (Glycyrrhiza glabra), known for its ulcer-healing properties. Herbal remedies, including aloe vera and deglycyrrhizinated licorice (DGL), have shown the potential to reduce ulcer symptoms and promote healing. Homeopathy offers remedies like Nux vomica and Carbo vegetabilis, aimed at relieving symptoms based on individual constitutions. Lifestyle changes, including minimizing NSAID use, alcohol, and smoking, complement these therapies. For complicated or refractory cases, surgical interventions, such as vagotomy or partial gastrectomy, may be necessary. Peptic ulcer disease (PUD) is a significant health concern due to its potential for complications and its impact on quality of life. Understanding the multifaceted nature of PUD necessitates a holistic approach that considers various factors beyond traditional medical interventions.